2015
DOI: 10.1186/s12936-015-0548-z
|View full text |Cite
|
Sign up to set email alerts
|

IL10A genotypic association with decreased IL-10 circulating levels in malaria infected individuals from endemic area of the Brazilian Amazon

Abstract: BackgroundCytokines play an important role in human immune responses to malaria and variation in their production may influence the course of infection and determine the outcome of the disease. The differential production of cytokines has been linked to single nucleotide polymorphisms in gene promoter regions, signal sequences, and gene introns. Although some polymorphisms play significant roles in susceptibility to malaria, gene polymorphism studies in Brazil are scarce.MethodsA population of 267 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
2
17
0
2
Order By: Relevance
“…Studies conducted in the United States with African-American and Caucasian populations found higher frequencies of 66% and 37% [76] and 48% and 25% [77], respectively. Our data showing the higher frequency of the mutant A allele are in agreement with studies in the Brazilian Amazon that found frequencies of 70.13% [21] and 73% [17] but all lacked an association with malaria caused by P. vivax or P. falciparum . Few studies have described an association between this SNP with malaria; however, its association with dermatitis was observed in India [78].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Studies conducted in the United States with African-American and Caucasian populations found higher frequencies of 66% and 37% [76] and 48% and 25% [77], respectively. Our data showing the higher frequency of the mutant A allele are in agreement with studies in the Brazilian Amazon that found frequencies of 70.13% [21] and 73% [17] but all lacked an association with malaria caused by P. vivax or P. falciparum . Few studies have described an association between this SNP with malaria; however, its association with dermatitis was observed in India [78].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, polymorphisms in cytokine genes can alter the production or activity of these proteins and consequently affect the inflammatory response to malaria [1618]. As a result, these polymorphisms may be associated with susceptibility to or progression of disease [17, 19]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations